SCORPION VENOM II PROCEDURES FOR OBTAINING AND PROPERTIES OF THE VENOM III EFFECTS IN MAN AND ANIMALS IV MECHANISMS OF THE PHYSIOLOGIC ACTIONS V MECHANISMS OF FATAL POISONING VI IMMUNOLOGY VII TREATMENT AND PROPHYLAXIS BIBLIOGRAPHY - MENDEZ PEREZ, TH (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1947)
A review of the properties of toxins and scorpion venom shows a resemblance in the production of antigens, adjustment to the law of multiple proportions, thermolability, and detoxification with formol Differing from most toxins, scorpion venom does not r
BOL INST ESTUD MED BIOL
Keywords: SCORPION VENOM, PROPERTIES, EFFECTS, MAN, ANIMALS, MECHANISMS, PHYSIOLOGIC, MECHANISMS, POISONING, IMMUNOLOGY, TREATMENT, PROPHYLAXIS, BIBLIOGRAPHY; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA